In vitro hepatic biotransformation of the algal toxin pectenotoxin-2. (June 2020) - Sandvik, Morten; Miles, Christopher O.; Wilkins, Alistair L.; Fæste, Christiane
Abstract: We have investigated the in vitro metabolism of pectenotoxin-2 (PTX-2) using primary hepatocytes from Wistar rats in suspension. Purified PTX-2 was rapidly metabolized. Two major and several minor oxidized PTX-2 metabolites were formed, none of which had retention times corresponding to PTX-1, -11, or −13. Hydrolysis products, such as PTX-2 seco acid, were not observed. Preliminary multi-stage LC-MS analyses indicated that the major hepatic PTX-2 metabolites resulted from the insertion of an oxygen atom at the positions C-19 to C-24, or at C-44. The rapid oxidative metabolism may explain the low oral toxicity of PTXs observed in vivo studies. Highlights: PTX-2 is rapidly metabolized in rat hepatocytes. Two major and several minor oxidized PTX-2 metabolites were formed. The results may explain the low oral toxicity of PTXs observed in vivo studies .